Chondrogenesis of mesenchymal stem cells: role of tissue source and inducing factors - Boeuf, Stephane; Richter, Wiltrud (Stem cell research & therapy, 2010)
Multipotent mesenchymal stromal cells (MSCs) are an attractive cell source for cell therapy in cartilage. Although their therapeutic potential is clear, the requirements and conditions for effective induction of chondrogenesis in MSCs and for the production of a stable cartilaginous tissue by these cells are far from being understood. Different sources of MSCs have been considered for cartilage tissue engineering, mainly based on criteria of availability, as for adipose tissue, or of proximity to cartilage and the joint environment in vivo, as for bone marrow and synovial tissues. Focussing on human MSCs, this review will provide an overview of studies featuring comparative analysis of the chondrogenic differentiation of MSCs from different sources. In particular, it will examine the influence of the cells' origin on the requirements for the induction of chondrogenesis and on the phenotype achieved by the cells after differentiation.
Gesehen am 02.02.2023